THE ROLE OF GENITAL TUBERCULOSIS IN THE STRUCTURE OF INFERTILITY - A. A. Abashidze; V. F. Arakelyan (Акушерство, гинекология и репродукция, 2016)
The problem of genital tuberculosis is very actual. Special attention deserves an increase the number of TB patients, aged 25-34 years – the age of peak fertility. The period from the beginning of the disease to establish a correct diagnosis is often reaches 5-20 years. Many years the patient can have only one complaint – infertility. The relevance of genital tuberculosis modern diagnostics is determined by the mismatch objective of increasing the prevalence of pulmonary tuberculosis and subjective low prevalence of urogenital tuberculosis associated with the complexity of its detection and treatment outcomes. Among the modern methods of immunodiagnostics tuberculosis, great importanceis the identification of specific antibodies to Mycobacterium tuberculosis in the peripheral blood by enzyme immunoassay and immunochromatographic rapid test.